Deficits in Cortical Suppression During Vocalization are Associated With Structural Abnormalities in the Arcuate Fasciculus in Early Illness Schizophrenia and Clinical High Risk for Psychosis. (29th November 2017) - Whitford, Thomas J; Oestreich, Lena K L; Ford, Judith M; Roach, Brian J; Loewy, Rachel L; Stuart, Barbara K; Mathalon, Daniel H
Abstract: Self-generated speech produces a smaller N1 amplitude in the auditory-evoked potential than externally generated speech; this phenomenon is known as N1-suppression. Schizophrenia patients show less N1-suppression than healthy controls. This failure to self-suppress may underlie patients' characteristic tendency to misattribute self-generated thoughts and actions to external sources. While the cause of N1-suppression deficits to speech in schizophrenia remains unclear, structural damage to the arcuate fasciculus is a candidate, due to its ostensible role in transmitting the efference copy of the motor plan to speak. Fifty-one patients with early illness schizophrenia (ESZ), 40 individuals at clinical high-risk for psychosis (CHR), and 59 healthy control (HC) participants underwent an electroencephalogram while they spoke and then listened to a recording of their speech. N1-suppression to the spoken sounds was calculated. Participants also underwent a diffusion-tensor imaging (DTI) scan, from which the arcuate fasciculus and pyramidal tract were extracted with deterministic tractography. ESZ patients exhibited significantly less N1-suppression to self-generated speech than HC participants, with CHR participants exhibiting intermediate levels. ESZ patients also exhibited structural abnormalities in the arcuate fasciculus—specifically, reduced fractional anisotropy and increased radial diffusivity—relative to both HC and CHR. There were no between-group differences in the structural integrity of the pyramidal tract. Finally, level of N1-suppression was linearly related to the structural integrity of the arcuate fasciculus, but not the pyramidal tract, across groups. These results suggest that the self-suppression deficits to willed speech consistently observed in schizophrenia patients may be caused, at least in part, by structural damage to the arcuate fasciculus.